Faculty diversity, equity, and inclusion in academic dentistry: Has dental education missed the call of #MeToo?. Issue 9 (27th September 2022) - Zarkowski, Pamela; Brady, Michelle; Saeed, Sophia G.
Abstract: Faculty, students, and staff experience sexual harassment in the workplace and educational environment. Frequently, the victim takes no action either due to a lack of understanding of their rights or concern about retaliation or adverse outcomes if an incident is reported. The #MeToo movement has enhanced awareness of sexual harassment and its impact on victims. However, dental institutions vary in their approach to creating an environment free from harassment and supportive of individuals subject to inappropriate or illegal behaviors. In this article, four vignettes provide examples of harassment, mistreatment, or bias. Common themes and critical issues within the vignettes are then identified, discussing the potentially illegal, unethical, inappropriate, and unprofessional behaviors and comments. Strategies to address the issues identified are described. Recommendations are also provided to assist dental institutions and educators in evaluating their current practices and policies and implementing change.